Ion Conducting Studies in PEO:NaI and its Composite: Carrier Density Approach - Mehrotra, Kushal; Singh, Divya; Bhattacharya, Bhaskar (Recent Innovations in Chemical Engineering, 2021)
Background: The modulation in electrical conductivity of polymer electrolyte, viz., polyethylene oxide (PEO) complexed with different concentrations of sodium iodide is studied. The role of mobility and charge concentration in the electrical conductivity of polymer electrolytes is established. Methods: The complex impedance spectroscopy (CIS) method is used to measure the electrical conductivity of film. Results: The effect on charge concentration, mobility and conductivity of PEO+NaI film by adding three different concentration of silicon is reported. Conclusion: The polarized optical microscopy (POM) is used to study the morphology of the surface of PEO, PEO+NaI films dispersed with Si.
Keywords: amorphicity